Effect of MgCl(2) and GdCl(3) on ORAI1 Expression and Store-Operated Ca(2+) Entry in Megakaryocytes - Zhou, Kuo (Int J Mol Sci, 2021)
In chronic kidney disease, hyperphosphatemia upregulates the Ca(2+) channel ORAI and its activating Ca(2+) sensor STIM in megakaryocytes and platelets. ORAI1 and STIM1 accomplish store-operated Ca(2+) entry (SOCE) and play a key role in platelet activation. Signaling linking phosphate to upregulation of ORAI1 and STIM1 includes transcription factor NFAT5 and serum and glucocorticoid-inducible kinase SGK1. In vascular smooth muscle cells, the effect of hyperphosphatemia on ORAI1/STIM1 expression and SOCE is suppressed by Mg(2+) and the calcium-sensing receptor (CaSR) agonist Gd(3+). The present study explored whether sustained exposure to Mg(2+) or Gd(3+) interferes with the phosphate-induced upregulation of NFAT5, SGK1, ORAI1,2,3, STIM1,2 and SOCE in megakaryocytes. To this end, human megakaryocytic Meg-01 cells were treated with 2 mM ß-glycerophosphate for 24 h in the absence and presence of either 1.5 mM MgCl(2) or 50 µM GdCl(3). Transcript levels were estimated utilizing q-RT-PCR, protein abundance by Western blotting, cytosolic Ca(2+) concentration ([Ca(2+)](i)) by Fura-2 fluorescence and SOCE from the increase in [Ca(2+)](i) following re-addition of extracellular Ca(2+) after store depletion with thapsigargin (1 µM). As a result, Mg(2+) and Gd(3+) upregulated CaSR and blunted or virtually abolished the phosphate-induced upregulation of NFAT5, SGK1, ORAI1,2,3, STIM1,2 and SOCE in megakaryocytes. In conclusion, Mg(2+) and the CaSR agonist Gd(3+) interfere with phosphate-induced dysregulation of [Ca(2+)](i) in megakaryocytes.